PSXI-28 Intake, digestibility and ruminal parameters in buffaloes fed sugarcane. (7th December 2018) - Pessoa, R; do Carmo, M; Alves, L; Costa, C; Pereira, K; Vieira, G; Neves, M; Silva, K; Bartolomeu, C
Abstract: This study aimed to evaluate intake, ruminal parameters and digestibility of nutrients in Murrah buffaloes. Four uncastrated male animals with an average initial body weight of 300.0 ± 15.6 kg and fitted with cannulas in the rumen were assigned to a 4 x 4 latin square design. Experimental diets consisted of the sugarcane (Saccharum officinarum L.) associated to concentrate (corn, wheat bran, soybean meal, urea and mineral) in the proportions of 20, 40, 60 and 80%. The diets were adjusted to contain 13.5% of crude protein and were supplied ad libitum, as a complete ration, twice daily. Each experimental period lasted 17 days, with the first thirteen days dedicated to animal adaptation. Rumen contents were collected every zero, two, four and six hours after afternoon feeding to measure pH and ammonia nitrogen. Total collection of feces was completed for three days in each period. The data were analyzed using the POC GLM and PROC REG procedure of SAS. The dry matter, organic matter, crude protein, ether extract and non fiber carbohydrates intakes increased linearly (P < 0.05) as the dietary levels of concentrate increased. Organic matter digestibility was affected (P < 0.05) by concentrate level and the maximum digestibility was estimated to be 69.9% with 48.8% of concentrate in the diet. The same trends were observed (P < 0.05) for apparent digestibility of dry matter, crude protein, ether extract, neutral detergent fiber and total carbohydrates. However, the organic matter digestibility with 80% of concentrate in the diet was 65.6%. Ammonia nitrogen was not altered (P > 0.05) by the treatments and ruminal pH decreased linearly (P < 0.05) (6, 42; 6.35; 6, 29 and 6, 28 for 20, 40, 60 and 80% of concentrate, respectively). It is concluded that up to 80% of concentrate could be associated to sugarcane in diets for buffaloes. Key Words: